Molecular analysis of NUT‐positive poromas and porocarcinomas identifies novel break points of YAP1:NUTM1 fusions. (12th July 2022) - Snow, Justin T.; Georgantzoglou, Natalia; Green, Donald C.; Parra, Ourania; LeBlanc, Robert E.; Yan, Shaofeng; Sriharan, Aravindhan; Momtahen, Shabnam; Winnick, Kimberley N.; Dimonitsas, Emmanouil; Stavrianos, Spiros; Lakiotaki, Eleftheria; et al.
Abstract: Background: Poromas, and their malignant counterparts, porocarcinomas, harbor recurrent translocations involving YAP1‐MAML2, YAP1‐NUTM1, and infrequently WWTR1‐NUTM1 ; YAP1‐NUTM1 being the most common in porocarcinomas. NUT immunohistochemistry (IHC) can be used to identify NUTM1 ‐translocated tumors. This study sought to investigate potential novel NUTM1 ‐fusion partners among NUT IHC‐positive poromas and porocarcinomas. Methods: Thirteen NUT IHC‐positive poroid tumors (four poromas and nine porocarcinomas) were identified within a multi‐institutional international cohort. Next‐generation sequencing (NGS) assessed for NUTM1 fusion partners. Results: NGS detected a NUTM1 fusion in 12 of 13 cases: YAP1‐NUTM1 (11/12 cases) and WWTR1‐NUTM1 (1/12 cases). Two of the cases (2/12) with NUTM1 fusion were not called by the NGS algorithm but had at least one read‐spanning YAP1‐NUTM1 break point upon manual review. A NUTM1 fusion was not identified in one case; however, the sample had low RNA quality. The following fusion events were identified: YAP1 exon 4:: NUTM1 exon 3 in six cases, YAP1 exon 6:: NUTM1 exon 2 in one case, YAP1 exon 3:: NUTM1 exon 3 in three cases, WWTR1 exon 3:: NUTM1 exon 3 in one case, and YAP1 exon 8:: NUTM1 exon 3 fusion in one case. Conclusion: While no novel NUTM1 fusion partners were identified within our cohort, 12 of 13 cases had discoverable NUTM1 fusions; YAP1‐NUTM1 fusion was detected in 11 cases (92%) and WWTR1‐NUTM1 in 1 case (8%). These data corroborate findings from other recent investigations and further substantiate the utility of NUT IHC in diagnosing a subset of poroid neoplasms. In addition, two of our cases harbored fusions of YAP1 exon 6 to NUTM1 exon 3 and YAP1 exon 8 to NUTM1 exon 2, which have not been reported before in poroid neoplasms and indicate novel break points of YAP1 .